Predictors of social functioning and quality of life in schizophrenia and autism spectrum disorder. (September 2021) - Corbera, Silvia; Wexler, Bruce E.; Bell, Morris D.; Pearlson, Godfrey; Mayer, Sophy; Pittman, Brian; Belamkar, Vaishali; Assaf, Michal
Highlights: Schizophrenia and autism have social cognitive and functioning deficits. Predictive power of empathy, IQ and symptoms on their functioning was examined. Both showed cognitive empathy deficits and only SZ had affective empathy deficits Negative symptoms but not empathy predicted functioning in schizophrenia & autism. Role of specific negative symptoms on outcomes must be studied to direct treatment Abstract: Schizophrenia (SZ) and Autism Spectrum Disorder (ASD) show overlap in social cognitive and functioning impairments. Proposed predictors of social functioning (SF) and quality of life (QL) have been symptom severity, IQ and social cognition. Empathy has rarely been compared between ASD and SZ and its predictive power on functional outcomes is unclear. We investigated general, affective, and cognitive empathy in 46 SZ, 30 ASD and 51 healthy controls (HC) and examined their relationship to SF and QL in addition to IQ and symptoms. SZ and ASD shared deficits in general and cognitive empathy, and personal distress, but only SZ showed deficits in affective empathy. Both groups showed lower performance-based empathy scores and only ASD showed slower responses compared to HC. Negative symptoms predicted QL in both groups, the more negative symptoms the worse QL (ASD t =-3.22; SZ t = -3.43; p <0.01), and only in ASD, IQ predicted QL, the higher the IQ the higher QL ( t = 2.1; p <0.05). In ASD only, negative symptoms predicted SF, the greater negative symptoms the worse SF ( t =-3.45; p <0.01), and communication deficits predicted SF, the higher deficits, the higher SF ( t = 2.9; p <0.01). Negative symptoms but not empathy were the shared predictors of functioning across ASD and SZ.